Clozapine dose for schizophrenia - Subramanian, Selvizhi; Völlm, Birgit A.; Huband, Nick (Wiley, 2017)
Background: Schizophrenia and related disorders such as schizophreniform and schizoaffective disorder are serious mental illnesses characterised by profound disruptions in thinking and speech, emotional processes, behaviour and sense of self. Clozapine is useful in the treatment of schizophrenia and related disorders, particularly when other antipsychotic medications have failed. It improves positive symptoms (such as delusions and hallucinations) and negative symptoms (such as withdrawal and poverty of speech). However, it is unclear what dose of clozapine is most effective with the least side effects. Objectives: To compare the efficacy and tolerability of clozapine at different doses and to identify the optimal dose of clozapine in the treatment of schizophrenia, schizophreniform and schizoaffective disorders. Search methods: We searched the Cochrane Schizophrenia Group’s Study-Based Register of Trials (August 2011 and 8 December 2016). Selection criteria: All relevant randomised controlled trials (RCTs), irrespective of blinding status or language, that compared the effects of clozapine at different doses in people with schizophrenia and related disorders, diagnosed by any criteria. Data collection and analysis: We independently inspected citations from the searches, identified relevant abstracts, obtained full articles of relevant abstracts, and classified trials as included or excluded. We included trials that met our inclusion criteria and reported useable data. For dichotomous data, we calculated the relative risk (RR) and the 95% confidence interval (CI) on an intention-to-treat basis based on a random-effects model. For continuous data, we calculated mean differences (MD) again based on a random-effects model. We assessed risk of bias for included studies and created ’Summary of findings’ tables using GRADE. Main results: We identified five studies that could be included. Each compared the effects of clozapine at very low dose (up to 149 mg/day), low dose (150 mg/day to 300 mg/day) and standard dose (301 mg/day to 600 mg/day). Four of the five included studies were based on a small number of participants. We rated all the evidence reported for the main outcomes of interest as low or very low quality. No data were available for the main outcomes of global state, service use or quality of life. Very low dose compared to low dose: We found no evidence of effect on mental state between low and very low doses of clozapine in terms of average Brief Psychiatric Rating Scale-Anchored (BPRS-A) endpoint score (1 RCT, n = 31, MD 3.55, 95% CI −4.50 to 11.60, very low quality evidence). One study found no difference between groups in body mass index (BMI) in the short term (1 RCT, n = 59, MD −0.10, 95% CI −0.95 to 0.75, low-quality evidence). Very low dose compared to standard dose: We found no evidence of effect on mental state between very low doses and standard doses of clozapine in terms of average BPRS-A endpoint score (1 RCT, n = 31,MD 6.67, 95%CI −2.09 to 15.43, very low quality evidence). One study found no difference between groups in BMI in the short term (1 RCT, n = 58, MD 0.10, 95% CI −0.76 to 0.96, low-quality evidence) Low dose compared to standard dose: We found no evidence of effect on mental state between low doses and standard doses of clozapine in terms of both clinician-assessed clinical improvement (2 RCTs, n = 141, RR 0.76, 95%CI 0.36 to 1.61, medium-quality evidence) and clinically important response as more than 30% change in BPRS score (1 RCT, n = 176, RR 0.93, 95% CI 0.78 to 1.10, medium-quality evidence). One study found no difference between groups in BMI in the short term (1 RCT, n = 57, MD 0.20, 95% CI −0.84 to 1.24, low-quality evidence). We found some evidence of effect for other adverse effect outcomes; however, the data were again limited. Very low dose compared to low dose: There was limited evidence that serum triglycerides were lower at low-dose clozapine compared to very low dose in the short term (1 RCT, n = 59, MD 1.00, 95% CI 0.51 to 1.49). Low dose compared to standard dose: Weight gain was lower at very low dose compared to standard dose (1 RCT, n = 27, MD −2.70, 95% CI −5.38 to −0.02). Glucose level one hour after meal was also lower at very lose dose (1 RCT, n = 58, MD −1.60, 95% CI −2.90 to −0.30). Total cholesterol levels were higher at very low compared to standard dose (1 RCT, n = 58, n = 58, MD 1.00, 95% CI 0.20 to 1.80). Low dose compared to standard dose: There was evidence of fewer adverse effects, measured as lower TESS scores, in the low-dose group in the short term (2 RCTs, n = 266, MD −3.99, 95% CI −5.75 to −2.24); and in one study there was evidence that the incidence of lethargy (RR 0.77, 95% CI 0.60 to 0.97), hypersalivation (RR 0.70, 95% CI 0.57 to 0.84), dizziness (RR 0.56, 95% CI 0.39 to 0.81) and tachycardia (RR 0.57, 95% CI 0.45 to 0.71) was less at low dose compared to standard dose. Authors’ conclusions: We found no evidence of effect on mental state between standard, low and very low dose regimes, but we did not identify any trials on high or very high doses of clozapine. BMI measurements were similar between groups in the short term, although weight gain was less at very low dose compared to standard dose in one study. There was limited evidence that the incidence of some adverse effects was greater at standard dose compared to lower dose regimes. We found very little useful data and the evidence available is generally of low or very low quality. More studies are needed to validate our findings and report on outcomes such as relapse, remission, social functioning, service utilisation, cost-effectiveness, satisfaction with care, and quality of life. There is a particular lack of medium- or long-term outcome data, and on dose regimes above the standard rate.